Elaboration of science teachers' technology-based lesson practices in terms of contextual factors influencing TPACK - KARACA, FERİDE (My University, 2022)
Background One of the important elements of teachers\" technology integration is Technological Pedagogical Content Knowledge (TPACK). Though there are studies on TPACK, limited information exists about its context element. This gap causes context-isolated studies for TPACK-related research. Purpose The aim of this research is to elaborate on science teachers\" technology-based lesson practices in terms of contextual factors influencing TPACK. Sample The study participants consisted of 12 science teachers and 7 educational technologists by using snowball sampling. Design and method The case study design method was used in this study within the qualitative research paradigm. The data was collected with semi-structured interviews by following the protocol for strategic performance problems. The interviews were examined employing content analysis to reveal the themes. Results and conclusions The findings of the study indicated that TPACK is not only a stand-alone knowledge and skills, but also it is context-oriented. The multifaceted factors represent components of a multi-layered structure of the context. These factors can be perceived by the teachers at different levels according to school types. Furthermore, sub-themes of the contextual factors showed complex interrelationships. This study contributes to the literature by revealing the sub-themes of the context and in-depth examination of contextual factors suggested for future studies.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Technology integration; technological pedagogical content knowledge; context; science teachers; educational technologists; PEDAGOGICAL CONTENT KNOWLEDGE; INTEGRATION PRACTICES; DESIGN; Technology integration; technological pedagogical content knowledge; context; science teachers; educational technologists